Gamma Knife Radiosurgery: An Overview of Physics, Chemistry, Biology and Neuro-medicine (Journal of Bangladesh College of Physicians and Surgeons, 2010)
The gamma knife is a highly specialized treatment unit thatprovides an advanced sophisticated stereotactic approachto treatment of tumour and vascular malformations withinthe internal structure of the head. The gamma knife deliversa single high dose of radiation emanating from 201 cobalt-60 unit sources. All 201 beam simultaneously intersect atthe same time in a pre-defined location. The treatmentplanning system for gamma knife radiosurgery has beendeveloped using nonlinear programming techniques. Thesystem optimizes the shot sizes, location and weights forgamma knife treatments. Open stereotactic technique in the1990’s was essential for the treatment of a number offunctional conditions and cystic space occupying lesions.It has an important part to play in the investigation oftumours and can help to increase the number which areaccessible to treatment. It can be employed to guide notonly solid instruments but also ionizing irradiation to “masslesion– targets”. It is just this combination of stereotacticguidance and narrow beam, high energy radiation toprecisely defined target, is the basis of gamma kniferadiosurgery . The topic on radiological physics presents abroad field, which includes physics of radiation therapy,diagnosis and nuclear medicine. The emphasis is on thebasic physical principles which form a common foundationfor these areas. Consequently, the topic provides both basicradiation physics, physical aspects of treatment planningand use of radiation beams. Some knowledge of the effectof ionizing radiation on living tissues is necessary, for thosewho wish to understand the nature of any treatment usingradiation and who also wish to inform patients about suchtreatment. The topic relates to the effects of radiation onvisible structures, in other words, cells and tissues. Theradiobiological knowledge described here has beendeveloped in relation to standard radiotherapy. Moreover,the linear quadratic model of cell killing is also applicablefor single dose irradiation.DOI: 10.3329/jbcps.v28i2.5370J Bangladesh Coll Phys Surg 2010; 28: 100-112